2016
DOI: 10.1103/physrevb.94.245312
|View full text |Cite
|
Sign up to set email alerts
|

Angular phase shift in polarization-angle dependence of microwave-induced magnetoresistance oscillations

Abstract: We examine the microwave frequency(f)-variation of the angular-phase-shift, θ 0 , observed in the polarization-angle-dependence of the microwave-induced magnetoresistance oscillations in the high mobility GaAs/AlGaAs two-dimensional electron system. By fitting the diagonal resistance R xx vs. θ plots to an empirical cosine square law, we extract the θ 0 and trace its quasi-continuous variation with f. The results suggest that the overall average of θ 0 extracted from Hall bar device sections

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“… 24 , 27 . The radiation-induced magnetoresistance oscillations, can be observed roughly over the interval −0.2 ≤ B ≤ 0.2 T (red-curve) 1 , 3 , 5 12 , 14 , 15 , 18 , 20 , 24 , 27 30 , 32 34 , 36 , 39 .
Figure 1 Radiation induced magnetoresistance oscillations in R xx in a GaAs/AlGaAs heterostructure 2D electron system.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 , 27 . The radiation-induced magnetoresistance oscillations, can be observed roughly over the interval −0.2 ≤ B ≤ 0.2 T (red-curve) 1 , 3 , 5 12 , 14 , 15 , 18 , 20 , 24 , 27 30 , 32 34 , 36 , 39 .
Figure 1 Radiation induced magnetoresistance oscillations in R xx in a GaAs/AlGaAs heterostructure 2D electron system.
…”
Section: Resultsmentioning
confidence: 99%
“…Such high quality material has demonstrated new 2D physical phenomena such as the photo-excited zero-resistance states 1 , 2 and 1/4− cycle shifted magnetoresistance oscillations 3 induced by low energy photons in the low magnetic field, high filling factor limit. Associated results have produced new interest in the experimental 1 39 and theoretical 40 62 study of photo-excited transport in low dimensional systems. The dark properties of the GaAs/AlGaAs 2D material system in the low magnetic field limit have also attracted recent experimental attention as the results have helped to provide new insights into both an observable giant magnetoresistance in the 2DES, and a small, narrow negative magnetoresistance near null magnetic field 63 77 .…”
Section: Introductionmentioning
confidence: 99%
“…The novel physical phenomena include both photo‐excited magneto transport effects and dark transport effects. Recent experimental and theoretical studies of high mobility GaAs/AlGaAs 2DES under low energy photo excitation, has demonstrated interesting novel photo‐excited magneto‐transport effects such as zero resistance states and associated radiation induced magnetoresistance oscillations. On the other hand, dark magnetoresistance properties, such as negative‐MR effects exhibited by high‐mobility samples, have also attracted experimental and theoretical interest among the researchers aiming to further understand the transport mechanism in these specimens …”
Section: Introductionmentioning
confidence: 99%